Community-based tourism: Concepts, opportunities and challenges - Prakoso, Aditha Agung; Pradipto, Eugenius; Roychansyah, Muhammad Sani; Nugraha, Bima Setya (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: The Community-Based Tourism (CBT) concept needs to be understood deeply. We need to know and predict the opportunities and challenges that exist and will occur in the future in developing the community and tourism as a mutualism. This research analyzed the theories to describe it and derive conclusions for the basic concepts of community-based tourism as well as further explore the cases of applying these concepts to gain opportunities and challenges from community-based tourism  Research Methodology: This research utilizes a conceptual approach based on a literature review. It critically evaluates existing theories, findings, and case studies on CBT to derive insights into its principles, opportunities, and challenges. Results: The study identifies the significance of social and cultural capital in CBT, emphasizing community participation and ownership. It also discusses the benefits and challenges, including economic development, cultural preservation, and issues such as resource dependence and environmental impact. Conclusions: While CBT offers a sustainable alternative to mass tourism, its success requires effective planning, community involvement, and resource management. Future research should focus on overcoming existing challenges to enhance the sustainability of CBT. Limitations: This study is a secondary data-based analysis (literature review) on the concept of community-based tourism in the social and cultural context of the community, as well as the opportunities and challenges of its application to tourism development Contributions: This study provides an in-depth and comprehensive view of community-based tourism to assist in exploring approaches and theories in community-based tourism research and planning and policymaking in the tourism sector, especially in the local community aspect.